2006
DOI: 10.1021/tx050356u
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry and Photocytotoxicity of Alkaloids from Goldenseal (Hydrastis canadensisL.). 2. Palmatine, Hydrastine, Canadine, and Hydrastinine

Abstract: Goldenseal is an herb that is widely used in dietary supplements, eye washes, and skin lotions. The presence of Goldenseal root powder in dietary supplements and the topical application of Goldenseal preparations raise the possibility that an adverse phototoxic reaction may result from an interaction between its constituent alkaloids and light in exposed tissues. We have previously shown that berberine, the major alkaloid in Goldenseal powder, in combination with UVA causes DNA damage and cell death in HaCaT k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 19 publications
2
18
0
Order By: Relevance
“…The S 1 state of these alkaloids immediately returns to the ground state via a nonradiative mechanism (22,23). This rapid deactivation should be the reason for the decreased 1 O 2 generation by photosensitized berberine and palmatine in an aqueous solution (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The S 1 state of these alkaloids immediately returns to the ground state via a nonradiative mechanism (22,23). This rapid deactivation should be the reason for the decreased 1 O 2 generation by photosensitized berberine and palmatine in an aqueous solution (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Alkaloids comprise a diverse group of heterocyclic nitrogen substances, being commonly considered high toxic molecules that play an important defensive role, but reflecting a general biological principle of poisonous plants (Inbaraj et al, 2001(Inbaraj et al, , 2006Sertel et al, 2011). Nevertheless, in some situations, their toxicity is benefic; for example, Sertel et al (2011) reported that vinblastine, vincristine (from Catharanthus roseus, formerly: Vinca rosea) and semisynthetic vindesine and vinorelbine, presented high cytotoxicity against cancer cells, highlighting the potential of these dimeric indole alkaloids for cancer, leukemia and lymphomas treatments.…”
Section: Secondary Metabolitesmentioning
confidence: 99%
“…6). The above cathodic wave is thought to relate to a one-electron transfer process, as described in Scheme 3 [15], in which the quaternary nitrogen is the electrochemical center. Because fluoride ions can interact with the electrochemical center, the incorporation of fluoride ions would therefore interfere with the conversion of palmatine into palmatine radicals in aprotic systems.…”
Section: Resultsmentioning
confidence: 99%